Problematika dalam Pembelajaran Kelas Daring Selama Masa Pandemi Covid-19 pada Mata Pelajaran IPA - Bahasuan, Nadya Rahmawati; Safnowandi, Safnowandi; Armiani, Sucika (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2022)
This study aims to find out the problems of online classroom learning during the Covid-19 pandemic in natural science subjects for students of SMP Negeri 2 Kediri, West Lombok Regency. The type of research used in this research is survey research with qualitative methods. The population of this research is the seventh grade students of SMP Negeri 2 Kediri for the academic year 2021/2022 as many as 24 students. The time and place of the research was carried out at SMP Negeri 2 Kediri, Street Wisata Banyumulek, Kediri District, West Lombok Regency in the odd semester of the 2021/2022 Academic Year. The research instrument used teacher interview sheets and student questionnaire sheets. Data collection techniques used teacher interview techniques to obtain data and information from teachers, and response questionnaires to find out the problems of online classroom learning. The results showed that the students' responses in classroom learning obtained 37.8% questionnaire results in the category of strongly agree, 36.6% in the agree category, 37.9% in the doubtful category, 55% in the disagree category, and 12% in the very category. don't agree. This shows that most students agree with online learning during the Covid-19 pandemic.